Enjoy! Assertive Language and Consumer Compliance in (Non)Hedonic Contexts - Ann Kronrod; Amir Grinstein; Luc Wathieu (European School of Management and Technology (ESMT), 2009)
This paper is concerned with the tension between consumer persuasion and freedom of choice. We study how assertive language (as in the slogan Just do it!) affects consumer compliance in hedonic vs. utilitarian contexts. Previous literature consistently claimed that forceful language would cause reactance and decreased compliance. However, we find in four studies that assertive persuasion is effective in contexts involving hedonic goods and hedonically framed utilitarian goods. Our hypotheses emerge from sociolinguistic research and confirm the relevance of linguistic research in consumer behavior.
urn:nbn:de:101:1-201106143639
Keywords: D18; M37; 650; assertive message; consumer compliance; hedonic consumption; utilitarian consumption; forceful language; persuasion; freedom of choice; reactance; Konsumentenverhalten; Werbepsychologie; Konsumgütermarketing; Sprache; Linguistik